Asthmatic Attacks against Specific Primary School Students in Baghdad, Iraq - Mohammed , Saad Abdul Kareem; Mohammed , Ali Saad Abdul Kareem; Jabbar, Esraa Ghazy (American Journal of Biomedicine and Pharmacy, 2025)
Background: Certain stimuli can readily irritate the lungs and airways in children with asthma. Potential causes include, for instance, breathing in pollen or getting a cold or other respiratory illness. Play, sports, school, and sleep can all be disrupted by the irritating daily symptoms of childhood asthma [1]. For certain children, untreated asthma may result in potentially fatal episodes. Although it has distinct consequences, childhood asthma is not distinct from adult asthma. The illness is the main cause of hospital stays, emergency department (ED) visits, and absences from school. Asthma in children is unfortunately incurable, and symptoms may last into adulthood. Children can, however, control symptoms and safeguard their growing lungs with the right care [2]. Objective: This short study aims to identify certain risk factors that may increase the probability of developing asthma in some children under the age of 11 at Alrussafa-Baghdad. Methods: This survey was conducted in Baghdad to determine the prevalence of asthma among primary school students aged 7 to 11, with an average age of 9 years. The study was conducted from October to December 2024 at Al-Ilwiyah Paediatric Teaching Hospital in Al-Rusafa, Baghdad. Sixty children were included, 30 with bronchial asthma and 30 without asthma, control groups were gathered using face-to-face questionnaires directed to the child’s parents following the clinical examination of children by the consultant paediatrician at the hospital’s outpatient clinic. Results: There was no significant difference (p-value > 0.05) in gender distribution between asthmatic and non-asthmatic teams, as measured by frequency percentage: male = (16, 53%) and female = (14, 47%). Males (18, 60%) and females (12, 40%) were non-asthmatic, respectively. In this study, the prevalence of bronchial asthma was 2.1% (p-value = 0.04), which is statistically significant (p < 0.05). Conclusions: This Questionnaire indicated that crowding index, non-breastfeeding, family social status, mother’s education, family smoking history, family history of asthma, and food hypersensitivity reaction were all significant risk variables for illness severity (p-value = 0.001, p-value < 0.05).